Millimeter-tall carbon nanotube arrays grown on aluminum substrates. (April 2018) - Miura, Shota; Yoshihara, Yu; Asaka, Mayu; Hasegawa, Kei; Sugime, Hisashi; Ota, Aun; Oshima, Hisayoshi; Noda, Suguru
Abstract: Millimeter-tall vertically aligned carbon nanotubes (VA-CNTs) were grown directly on Al substrates. Atmospheric pressure chemical vapor deposition is performed at 600 °C, which is well below the melting point of Al (660 °C), using Fe catalyst and C2 H2 as a highly reactive carbon feedstock. The CNT height was sensitive to the C2 H2 concentration and 0.06 vol% was optimum for balanced growth rate and catalyst lifetime, yielding 0.06 mm-tall VA-CNTs in 2 h. The CO2 addition at 1.8 vol% to the C2 H2 /Ar gas significantly enhanced the CNT growth, yielding 1.1 mm-tall VA-CNTs in 12 h. CO2 shows this remarkable effect when added in large excess to C2 H2, differently from the well-known method of "small addition of water." Moreover, the resulting VA-CNTs showed electrical contact with the Al sheets with resistance of ≤0.7 Ω cm −2 . The effect of CO2 is systematically studied and discussed. Graphical abstract: Image 1